Highly efficient Ag-alloyed Cu(In, Ga)Se2 solar cells with wide bandgaps and their application to chalcopyrite-based tandem solar cells. (June 2018) - Kim, Kihwan; Ahn, Seung Kyu; Choi, Jang Hoon; Yoo, Jinsoo; Eo, Young-Joo; Cho, Jun-Sik; Cho, Ara; Gwak, Jihye; Song, Soomin; Cho, Dae-Hyung; Chung, Yong-Duck; Yun, Jae Ho
Abstract: In this work, Ag alloying effects in wide-bandgap Cu(In, Ga)Se2 (CIGS) solar cells are investigated, and their application in tandem solar cells is attempted. With a three-stage process, highly efficient Ag-alloyed CIGS (ACIGS) solar cells with Eg ≥ 1.4 eV are fabricated; the benefits of Ag alloying are discussed with a focus on the control of structural/electronic disorders. The ACIGS solar cells are found to exhibit particularly improved device performance in specific compositions; in general, Ag alloying helps to enhance VOC in wide-bandgap CIGS solar cells. With wide-bandgap ACIGS cells as a top subcell, various kinds of chalcopyrite-based tandem (two-junction and two-terminal) cells are demonstrated. Prospects and limitations of chalcopyrite-based tandem cells are investigated by examining beam-splitting tandem, mechanically stacked tandem, and monolithic tandem cells. Graphical abstract: Ag-alloyed chalcopyrite solar cells with wide bandgaps (Eg ≥ 1.4 eV) exhibit enhanced device performance; various kinds of tandem devices using the Ag-alloyed cells are presented. fx1 Highlights: Ag alloying into CIGS is attempted for reduced electronic/structural disorder. Ag-alloyed CIGS (Eg ≥ 1.4 eV) solar cells exhibit enhanced device performance. Highly efficient ACIGS cells are employed as the top subcell in a tandem cell. Various kinds of chalcopyrite-based tandem cells are demonstrated.